Integrating GeoGebra with Interactive Flat Panels: The Mediating Role of Student Engagement in Spatial Geometry Learning Outcomes - Susti Miara; Fery Muhamad Firdaus (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Solid geometry learning in elementary schools remains challenging because its abstract nature makes three-dimensional objects difficult to visualize. This study examined the effect of GeoGebra-Interactive Flat Panel (GeoGebra-IFP) integration on solid geometry learning outcomes, with Student Engagement as a mediating variable. A quantitative one-group pretest-posttest design involved 41 fifth-grade students. Data were collected through a UTAUT2-based GeoGebra-IFP integration questionnaire, a Student Engagement questionnaire covering behavioral, emotional, cognitive, and agentic engagement, a learning achievement test, and classroom implementation observation sheets. The data were analyzed using descriptive statistics, assumption tests, and path-analysis-based mediation with bootstrapping. The results showed that GeoGebra-IFP integration positively affected learning outcomes and Student Engagement. Student Engagement also positively affected learning outcomes and significantly mediated the relationship between GeoGebra-IFP integration and solid geometry learning outcomes. These findings indicate that interactive learning technology improves achievement both directly and indirectly by strengthening students’ engagement during instruction. Therefore, GeoGebra-IFP can be considered an innovative instructional medium for improving the quality of solid geometry learning in elementary schools.